Multiclass emotion classification by using Spectrogram image analysis: A CNN-XGBoost fusion approach - Esha, Ishraq Ahmed; Rahman, Shahrin; Chowdhury, Sayem Kader; Mim, Jannatul Ferdous (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.